2013
DOI: 10.3390/toxins6010108
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Cytolytic Cnidarian Venoms. A Review on Health Implications and Possible Therapeutic Applications

Abstract: The toxicity of Cnidaria is a subject of concern for its influence on human activities and public health. During the last decades, the mechanisms of cell injury caused by cnidarian venoms have been studied utilizing extracts from several Cnidaria that have been tested in order to evaluate some fundamental parameters, such as the activity on cell survival, functioning and metabolism, and to improve the knowledge about the mechanisms of action of these compounds. In agreement with the modern tendency aimed to av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 182 publications
(239 reference statements)
0
71
0
3
Order By: Relevance
“…Results showed that the two diterpenes plamonine F and palmonine D exhibited prominent apoptotic activity and induced growth regression of spheroids over ten days of incubation. Few reports have focused on the cytotoxicity of diterpenes, despite more than 40 eunicellan-type diterpenes have been isolated from gorgonian Acalycigorgia, Muricella, Briareum, Erythropodium and Eunicella [47]. Ortega et al [48] showed that palmonines isolated from the gorgonian Eunicella verrucosa presented cytotoxicity to human cancer cells (A549 lung carcinoma, HT29 colon carcinoma, and MEL28 melanoma).…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the two diterpenes plamonine F and palmonine D exhibited prominent apoptotic activity and induced growth regression of spheroids over ten days of incubation. Few reports have focused on the cytotoxicity of diterpenes, despite more than 40 eunicellan-type diterpenes have been isolated from gorgonian Acalycigorgia, Muricella, Briareum, Erythropodium and Eunicella [47]. Ortega et al [48] showed that palmonines isolated from the gorgonian Eunicella verrucosa presented cytotoxicity to human cancer cells (A549 lung carcinoma, HT29 colon carcinoma, and MEL28 melanoma).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased activity of glutathione reductase and increased levels of glutathione transferase parallel the decrease in GSH, indicating an increase in oxidative stress in toxin-exposed animals. As reported recently by Mariottini and Pane [7], several cnidarian venoms have been found to have cytotoxic properties. In this regard, Soletti et al [50] showed that the cytolysins EqTx-II and Bc2 from the sea anemone Sagartia rosea potentiated cytotoxicity in human glioblastoma cells through a necrosis-like cell death.…”
Section: Discussionmentioning
confidence: 57%
“…Pharmaceutical studies have demonstrated that the venom of several species of sea anemones produces different symptoms and modes of toxicity. Studies of inflammation and allergic reactions [3] hemolytic activities [4], immunomodulating activities [5], cardiotoxicity [6], and cytolytic effects [7] have all produced interesting outcomes. Moreover, the incidence of neurotoxicity reactions such as convulsions, paralysis, respiratory failure, cardiovascular reactions, and stroke [6,8] is mostly recognized.…”
Section: Introductionmentioning
confidence: 99%
“…5,[39][40][41][42][43] In addition, the activity of crude venom on other cnidarians has been assessed.…”
Section: Toxicological Aspectsmentioning
confidence: 99%